Do hours restrictions matter? A discrete family labor supply model with endogenous wages and hours restrictions - Elke Wolf (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
The labor supply of West German married and cohabiting couples is analyzed using a discrete choice model. Following van Soest (1995), the labor supply decision is based on a household utility function which is determined by the leisure of the two spouses and net household income. Furthermore, heterogeneity of preferences and the German tax and benefit system are taken into account. We extend the neoclassical labor supply model in two directions. First, we allow for endogenous wages and find that there exist substantial wage differences between part-time and full-time jobs. In view of the negative wage differentials of part-time jobs, the model with endogenous wages predicts lower part-time employment than the standard neoclassical model. Compared with the distribution of actual hours worked, the share of part-time jobs is highly underpredicted. In a second step, hours restrictions are accommodated, as a result of which the estimated wage elasticities of both spouses are substantially reduced.
Keywords: J22; C25; 330; Arbeitsangebot; Haushaltsökonomik; Familienökonomik; Arbeitszeit; Geschlecht; Schätzung; Deutschland